2019
DOI: 10.1097/md.0000000000016301
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of acupuncture for knee osteoarthritis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 35 publications
1
57
2
Order By: Relevance
“…In another trial, patients with lower KOA Kellgren grades could gain more benefits from electroacupuncture in pain relief and physical functions improvements [ 29 ]. An overview of systematic reviews suggested that the effectiveness of electroacupuncture prevailed over that of western medicine with respect to Lequesne index [ 32 ]. Furthermore, through three-dimensional motion analysis, electroacupuncture was verified to increase the speed of ascending and descending stairs of KOA patients in a trial [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another trial, patients with lower KOA Kellgren grades could gain more benefits from electroacupuncture in pain relief and physical functions improvements [ 29 ]. An overview of systematic reviews suggested that the effectiveness of electroacupuncture prevailed over that of western medicine with respect to Lequesne index [ 32 ]. Furthermore, through three-dimensional motion analysis, electroacupuncture was verified to increase the speed of ascending and descending stairs of KOA patients in a trial [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] However, there is no consensus on the best therapeutic schedule to improve the symptoms of KOA at present, as the conventional western medicine used to treat KOA is accompanied by various of side effects. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…In particular, acupuncture therapy has a definitive effect on improving symptoms and movement (14,15). In an overview of systematic reviews published in 2019, which examined the effects of acupuncture therapy on chronic knee pain due to osteoarthritis, acupuncture therapy was reported to demonstrate more total effective rate, short-term effective rate and less adverse reactions than western medicine of high quality outcomes (16).…”
Section: Introductionmentioning
confidence: 99%